Effect of a new calcium antagonist, tiapamil, in hypertension of the elderly. - Balansard, P (1984)
The antihypertensive effect of a single oral dose of tiapamil (450 mg) and placebo were compared in a single blind randomized cross-over study in 10 71-86 year old hypertensive patients. Blood pressure (BP) and heart rate (HR) were recorded every 15 min for 12 h by an automatic device. Tiapamil led to a decrease in mean daytime systolic (SBP) and diastolic (DBP) BP from 171 +/- 12/98 +/- 10 mm Hg to 159 +/- 11/90 +/- 9 mm Hg (P less than 0.001) without significant variation in HR. Thereafter patients received tiapamil 450 twice daily; by the seventh day of treatment mean daytime SBP and DBP were 155 +/- 13/85 +/- 14 mm Hg (P less than 0.001 vs placebo). The hourly mean values of SBP recorded for 8/12 h (first tiapamil day) and 10/12 h (seventh tiapamil day) were significantly lower than the corresponding values after placebo. We conclude that tiapamil in the elderly exerts a sustained antihypertensive effect lasting 12 h or more, with only minor variations in HR. This effect predominates on systolic pressure and is significant from the first dose.